Pengaruh Pemahaman Agama Islam terhadap Perilaku Sosial Siswa di SMP Negeri 1 Ciomas - Fida Khotimah; M. Kholil Nawawi; Abrista Devi (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
The way students behave today needs serious attention. Because many things are not in accordance with the understanding of Islam that is shown in the family and at school, it is due to a lack of understanding of Islam by students. This study aims to determine 1). Understanding of Islam in class VIII at SMP Negeri 1 Ciomas, 2). Social Behavior of Class VIII students at SMP Negeri 1 Ciomas, and 3). The influence of Islamic religious understanding on the social behavior of eighth grade students at SMP Negeri 1 Ciomas. The approach used is quantitative with a survey method, namely a data collection carried out in the form of a questionnaire/questionnaire, which is then disseminated to respondents. The selected respondents are the return of 59 students of class VIII. The results of this study indicate that the understanding of Islam in class VIII is in the good category. This is based on the number of respondents' answers with the answer "Strongly Agree" 65.3%, the answer "Agree" 28.0%, the answer "Doubtful" 10.6%, and for the answer "Disagree" 16.6%. Class VIII Social Behavior in good category. This is based on the number of respondents' answers with the answer "Strongly Agree" 31.6%, the answer "Agree" 26.2%, the answer "Doubtful" and the answer "Disagree" 30.4%. From the simple linear regression test (ANOVA test) that the results of Fcount = 8.214 with a significant value of 0.006 <0.05 so it can be ascertained that Religious Understanding has an effect on Students' Social Behavior. Then based on the coefficient test, the Constant (a) value of 1.875 shows that when Religious Understanding (X) is feasible or not increasing, Social Behavior (Y) will still be worth 1.875. Then, the value of the regression coefficient (B) is 0.344, which indicates a unidirectional effect. That is, if the understanding of religion increases by one unit, it will increase behavior by 0.344 units with a significant 0.006 <0.05 so that it can guarantee that religious understanding has an effect on students' social behavior. Keywords: Understanding of Islam, Social Behavior.